The Influence of Eating at Home on Dietary Diversity and Airway Inflammation in Portuguese School-Aged Children - de Castro Mendes, F (2021)
Considering the negative impact of a lack of dietary diversity on children's nutritional status, we aimed to describe dietary variety according to eating at home frequency and assessed its association with respiratory outcomes in school-aged children. This cross-sectional study included 590 children (49% girls) aged 7 to 12 years from 20 public schools located in city of Porto, Portugal. Daily frequency of eating at home groups were calculated and dietary diversity was calculated using a 10-food group score from a 24 h recall questionnaire. Spirometry and exhaled nitric oxide levels (eNO; <35 and >= 35 ppb) were assessed. The comparison of diet diversity according to the groups was performed by ANOVA and ANCOVA. The association between dietary diversity and respiratory outcomes was examined using regression models. In multivariate analysis, children in the highest group of eating at home episodes (>= 4 occasions) obtained the lowest dietary diversity mean score, while the lowest group (<2) had the highest mean score (p-value 0.026). After adjustment for confounders, higher diet diversity (>= 5 food groups) significantly decreased the odds of having an eNO >= 35. Diet diversity might decrease the chance of airway inflammation among children. However, having more eating episodes at home could be a barrier to a more diverse diet.